Highly Robust but Surface‐Active: An N‐Heterocyclic Carbene‐Stabilized Au25 Nanocluster. (23rd October 2019) - Shen, Hui; Deng, Guocheng; Kaappa, Sami; Tan, Tongde; Han, Ying‐Zi; Malola, Sami; Lin, Shui‐Chao; Teo, Boon K.; Häkkinen, Hannu; Zheng, Nanfeng
Abstract: Surface organic ligands play a critical role in stabilizing atomically precise metal nanoclusters in solutions. However, it is still challenging to prepare highly robust ligated metal nanoclusters that are surface‐active for liquid‐phase catalysis without any pre‐treatment. Now, an N‐heterocyclic carbene‐stabilized Au25 nanocluster with high thermal and air stabilities is presented as a homogenous catalyst for cycloisomerization of alkynyl amines to indoles. The nanocluster, characterized as [Au25 ( i Pr2 ‐bimy)10 Br7 ] 2+ ( i Pr2 ‐bimy=1, 3‐diisopropylbenzimidazolin‐2‐ylidene) (1 ), was synthesized by direct reduction of AuSMe2 Cl and i Pr2 ‐bimyAuBr with NaBH4 in one pot. X‐ray crystallization analysis revealed that the cluster comprises two centered Au13 icosahedra sharing a vertex. Cluster 1 is highly stable and can survive in solution at 80 °C for 12 h, which is superior to Au25 nanoclusters passivated with phosphines or thiols. DFT computations reveal the origins of both electronic and thermal stability of 1 and point to the probable catalytic sites. This work provides new insights into the bonding capability of N‐heterocyclic carbene to Au in a cluster, and offers an opportunity to probe the catalytic mechanism at the atomic level. Abstract : Ein atomar präziser NHC‐stabilisierter Au25 ‐Nanocluster, der in einer Eintopfreaktion synthetisiert wird, weist eine wesentlich höhere thermische Stabilität in der Lösungsform auf als Au25, das durch Thiol‐ oder Phosphinliganden geschützt ist. Der Cluster zeigt eine ausgezeichnete katalytische Aktivität als homogener Katalysator in der Cycloisomerisierung von Alkinylamin.